Innovation Capability Model by Integrating Entrepreneurial Orientation, Market Orientation, Empowerment and SME Business Performance - Jiwa, I Dewa Nyoman Arta; Andika, Ary Wira (Dinasti Publisher, 2025)
The rapidly changing business environment, requires companies to maintain their performance through sustainable competitive advantage through effective resource utilization. The aim of this study is to explain for the necessity of developing the innovation capability model by integrating entrepreneurial orientation, market orientation, empowerment and business performance at levels of the SME business model. The paper is conceptual in approach. A keyword-based approach was used to select relevant articles from major journals to collect evidences and develop a conceptual model. The paper describes the innovation capability model by integrating entrepreneurial orientation, market orientation, empowerment and business performance. This has several implications for analysis of the innovation capability-business performance relationship.